STUDI TATA AIR DI SUB DAS BATI-BATI DAS MALUKA KALIMANTAN SELATAN - Rahman Rahman; Syarifuddin Kadir; Badaruddin Badaruddin (Jurnal Sylva Scienteae, 2020)
Watersheds that are scattered throughout the territory of Indonesia, constitute a whole natural ecosystem that is intact from the mountainous ecosystem in the upstream to the downstream coastal ecosystem. The area of critical land in South Kalimantan increased to 761,042.6 ha. Critical land maps show that most of the land in the Maluka watershed belongs to the Critical Somali group with an area of 55,214.73 ha and critical land 10,369.88 ha, in which the function of the forest area is a serious threat to the carrying capacity of the watershed. The purpose of this study is to determine the flow regime coefficient, annual flow coefficient, and water use index in the Bati-Bati watershed of the Maluka Watershed. The research method that is carried out by data collection is data of water discharge, water level, and river flow velocity. Analysis of the data used is the study through giving weight, class assignment, score calculation, and assessment of each sub criteria for determining watershed classification. The Flow Regime Coefficient value is 11.89 with a score of 1.00 rating criteria into the "medium" qualification. Annual Flow Coefficient 0.64 with a score of 1.50 which entered the recovery qualification "very high". Water use index value in April 2018 was 0.460 with a score of 0.75 which was included in the "low" recovery qualification and in May 2018 it was 0.663 with a score of 1.00 which was included in the "medium" recovery qualification.